2020
DOI: 10.18632/aging.102757
|View full text |Cite
|
Sign up to set email alerts
|

The association between monocyte to high-density lipoprotein ratio and hemorrhagic transformation in patients with acute ischemic stroke

Abstract: Hemorrhagic transformation (HT) is a common complication in patients with acute ischemic stroke. We investigated whether the monocyte to high-density lipoprotein ratio (MHR) is related to HT. Consecutive patients with ischemic stroke within 24 h of symptom onset were included in this study. HT was diagnosed by follow-up brain imaging after admission, and was classified as asymptomatic or symptomatic according to whether patients showed any neurologic worsening. Logistic regression was performed to estimate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 37 publications
0
19
2
Order By: Relevance
“…At the same time, HDL can recruit new endothelial cells to injured vascular endothelium, thereby promoting its repair (Riwanto et al, 2015). Contrary to our findings, another study associated higher MHR with lower risk of HT in patients with ischemic stroke (Wang et al, 2020). It is possible that this discrepancy reflects the different functions of different monocyte subpopulations in the two studies.…”
Section: Discussioncontrasting
confidence: 99%
“…At the same time, HDL can recruit new endothelial cells to injured vascular endothelium, thereby promoting its repair (Riwanto et al, 2015). Contrary to our findings, another study associated higher MHR with lower risk of HT in patients with ischemic stroke (Wang et al, 2020). It is possible that this discrepancy reflects the different functions of different monocyte subpopulations in the two studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Elevated MHR has also been found to be associated with a higher risk of HT in those patients undergoing MT ( 47 ). But another study showed that elevated MHR was associated with a lower risk of HT in ischemic stroke patients ( 22 ). In addition, a study on MHR and prognosis of acute ischemic stroke showed that non-surviving patients had higher MHR levels, and a high MHR value was an independent risk factor for 30-day mortality in patients with acute ischemic stroke ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study found that high MHR level was related to the poor functional prognosis of patients with acute ischemic stroke, especially the stroke subtype of LAA (21). Other studies based on patients with ischemic stroke showed that elevated MHR level was associated with high mortality but a low risk of hemorrhagic transformation (22,23). Indeed, there are few studies on the correlation between MHR and ischemic stroke, especially LAA ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Because monocyte counts did not change during AIS, the counts cannot predict long-term mortality ( 79 , 80 ). A recent investigation demonstrated that lower MHRs were independently associated with increased HT risk, especially sICH in AIS patients ( 81 ). The possible explanation for these paradoxical results may be the functional heterogeneity.…”
Section: Role Of Peripheral Immune Cells In the Disruption Of Bbb In Strokementioning
confidence: 99%